2012
DOI: 10.1007/s10875-012-9672-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38 MAPK Reduces Expression of Vascular Endothelial Growth Factor in Allergic Airway Disease

Abstract: These results indicate that inhibition of p38 MAPK may attenuate allergen-induced airway inflammation and vascular leakage through modulation of VEGF expression in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…The MAPKs subfamilies include the extracellular signal‐regulated kinases (ERK), further subclassified as ERK1/2, ERK3/4, ERK5 and ERK6/7, the c‐Jun NH 2 ‐terminal kinases (JNK), and the p38 MAPK, of which ERK1/2, JNK, and p38 MAPK are expressed in neutrophils . The p38 MAPK pathway has been shown to regulate proinflammatory angiogenesis, cytokine and chemokine expression, and synthesis by local cells and neutrophils in the lung . PI3Ks are a family of intracellular kinases activated by a number of molecules and stressing events for the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPKs subfamilies include the extracellular signal‐regulated kinases (ERK), further subclassified as ERK1/2, ERK3/4, ERK5 and ERK6/7, the c‐Jun NH 2 ‐terminal kinases (JNK), and the p38 MAPK, of which ERK1/2, JNK, and p38 MAPK are expressed in neutrophils . The p38 MAPK pathway has been shown to regulate proinflammatory angiogenesis, cytokine and chemokine expression, and synthesis by local cells and neutrophils in the lung . PI3Ks are a family of intracellular kinases activated by a number of molecules and stressing events for the cell.…”
Section: Discussionmentioning
confidence: 99%
“…12,42 The p38 MAPK pathway has been shown to regulate proinflammatory angiogenesis, cytokine and chemokine expression, and synthesis by local cells and neutrophils in the lung. 36, [43][44][45][46] PI3Ks are a family of intracellular kinases activated by a number of molecules and stressing events for the cell. They are involved in regulation of cellular proliferation, cell cycle, differentiation, apoptosis, and gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, VEGF is a mediator of vascular and extravascular remodeling, and plays a crucial role in Th2-mediated inflammation (107). With many reports that an increase in VEGF level has been observed in tissues and biological samples from individuals with asthma (115)(116)(117), mounting evidence has demonstrated that VEGF is a pivotal player in the pathogenesis of various airway disorders (107,118,119). As for HIF-1a/ HIF-2a, they have been well known as a transcriptional factor for VEGF in various pathologic conditions.…”
Section: Role Of Igfbp-3 In the Pathogenesis Of Asthmamentioning
confidence: 99%
“…As for HIF-1a/ HIF-2a, they have been well known as a transcriptional factor for VEGF in various pathologic conditions. Determination of HIF-1a and/or HIF-2a protein level in nuclear extracts has revealed that these protein levels are increased in several pulmonary inflammations, including allergen-induced asthma or exogenous oxidant-inhaled lung injury (118)(119)(120)(121)(122). On the basis of these observations, the control of HIF/VEGF signaling via the IGFBP-3 and IGF-I system seems to be promising for the development of therapeutics for inflammatory lung disorders.…”
Section: Role Of Igfbp-3 In the Pathogenesis Of Asthmamentioning
confidence: 99%
“…Delivering ONs to the lungs using polymer carriers represents a novel therapeutic approach to the treatment of inflammatory lung diseases (Kim et al, 2012) such as asthma. Paula et al (2011) reported that the enhanced efficiency of non-viral vector transfection was relative to ROS production using a therapeutic ultrasound.…”
Section: Discussionmentioning
confidence: 99%